2016
DOI: 10.1016/j.gtc.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Gastric Cancer

Abstract: Synopsis Gastric Cancer (GC) is 3rd leading cause of cancer related death worldwide; only 28.3% of are expected to survive >5 years. Although GC incidence has declined in the US during the last decade, an increase in the incidence of GC has been estimated for 2016. GC risk factors include, male gender, having >60 years, infectious agents such as H. pylori, GC family history, certain occupations, tobacco use, and diet, among others. Prognosis of GC is largely dependent on the tumor stage at diagnosis and classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 98 publications
(103 reference statements)
3
89
0
7
Order By: Relevance
“…Gastric cancer (GC) represents one of the commonest human malignancies characterized by an adverse clinical outcome (1). Radical surgery may be the only hope for curing GC in the stage of precursor lesions (2). However, even after surgical resection, radiotherapy and chemotherapy provide little benefit (3).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) represents one of the commonest human malignancies characterized by an adverse clinical outcome (1). Radical surgery may be the only hope for curing GC in the stage of precursor lesions (2). However, even after surgical resection, radiotherapy and chemotherapy provide little benefit (3).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in surgical techniques and the medical treatment of DGC, the prognosis of patients with DGC remains relatively poor, in the absence of reliable early diagnostic markers and therapeutic targets for the suppression of tumor metastasis 46. The 5-year survival rate remains low 79. DGC has poorer prognosis, and occurs more frequently in younger individuals with GC 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…From a global perspective, there is significant geographical diversity in the incidence of EGC and the survival rate for gastric cancer. In the US, most gastric cancers are found as advanced disease, and the overall 5-year survival rate is less than 30 % [5]. Recently, a 15-year follow-up population-based cohort study performed in Japan revealed that gastric cancer mortality was reduced by 67 % by endoscopic screening compared with radiographic screening [6].…”
Section: Detecting Gastric Cancer Earliermentioning
confidence: 99%